Método jurídico axiológico aplicado ao direito civil - Bolwerk, Aloísio Alencar (Pontíficia Universidade Católica de Minas Gerais, 2017)
The present work analyzes the juridical hermeneutics between positivism and post-positivism in order to present as product the axiological juridical method as new form of scientific knowledge to be used in civil law. For its formulation, it was necessary to go through the positivist thought, which gained strength by the simplification it promoted to the law, as well as the post-positivist current, grounded on evaluative interpretations that end up refining a reflective hermeneutics on ideas of justice. The law assumes functional drapery and the proposal of open society is incorporated to permeate juridical edification adjusted to social reality. The teleology of this conjugation is to withdraw the simple logical-deductive application to seek a new rationality in tune with the idea of material protection and concretizing rights. This diapason is where the dialogical plot of the "open society" enables the building of a civil law that is communicative with other sources. However, theories like the dialogue of sources and hetero-reflexive hermeneutics were pointed, but criticized, whether by lack of content, or because they promoted regress to the constructs of the positivist model. The interpretation of the Civil Code, from the axiological juridical method, values and chases the measurement between the desired justice and the necessary security, task which parts from the standard norm content, which forming essay passes between the action radius of the three "Communicating Entities": Society, State and Law and that permeates the construction of the normativism, which corresponds to an all interpretive transdisciplinary character. The axiological juridical method aims the evaluative construction of thought supported on the reflexes that can bear fruit for individuals and for society. Differs from judgment of equity by being operational and not dwelling on justice on abstract plan. Thus, its tailpiece is processed when it does the conjugation of judgments of value and reality (judgments of adequacy), which its concreteness can be perceived in face of the analysis of factual and hypothetical situations, where the method can be contextualized.